1973
DOI: 10.1139/o73-208
|View full text |Cite
|
Sign up to set email alerts
|

Novel Catalatic Proteins of Bakers' Yeast. I. An Atypical Catalase

Abstract: At any stage of growth of a wild-type bakers' yeast, some 20% of the catalatic activity of crude extracts is not precipitable by means of antibody prepared against the typical catalase (catalase T), whose purification and properties have been previously described. Some of this catalatic activity is due to the presence of an atypical catalase (catalase A), a heme protein, with a molecular weight estimated as 170 000 – 190 000, considerably lower than that of the usual catalases (225 000 – 250 000). Preparations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…1) Extracts from cells transformed with plasmid hybridized to YEp13-51 lacked catalase T activity completely, d were phos-whereas the transformants clearly showed cataumin (69,000), lase activity in a colony test. From this finding, drase (30,000). it was tentatively concluded that this plasmid nd catalase A, contains an incomplete catalase T gene coding for an altered catalase T protein that is sufficiently stable in intact cells but unstable in {as bound to extracts.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…1) Extracts from cells transformed with plasmid hybridized to YEp13-51 lacked catalase T activity completely, d were phos-whereas the transformants clearly showed cataumin (69,000), lase activity in a colony test. From this finding, drase (30,000). it was tentatively concluded that this plasmid nd catalase A, contains an incomplete catalase T gene coding for an altered catalase T protein that is sufficiently stable in intact cells but unstable in {as bound to extracts.…”
Section: Resultsmentioning
confidence: 76%
“…The yeast Saccharomyces cerevisiae contains two main catalase proteins called catalase T and catalase A (30,31). The regulation of these proteins by glucose, oxygen, and heme, their prosthetic group, has been studied by translation in vitro of total yeast mRNA and immunological detection of catalase proteins synthesized by the cell-free system (17,26).…”
mentioning
confidence: 99%
“…In Saccharomyces cerevisiae cells, two different types of catalase have been found (Traczyk et al 1985;Skoneczny and Rytka, 2000), which were designated catalase type A and catalase type T * Corresponding autor (Seah et al 1973). The two enzymes are encoded by different genes (CTA1 and CTT1 respectively), possessing independent control and being localized in different compartments: catalase T is a cytoplasm enzyme whereas catalase A is localized in peroxisomes (Lapinskas et al 1993).…”
mentioning
confidence: 99%
“…The yeast Saccharomyces cerevisiae contains two different hemoprotein catalases, the peroxisomal catalase A (32), which is encoded by the CTAI gene (11), and the cytoplasmic catalase T (33), encoded by CTTJ (35). Like the CYC1 (iso-1-cytochrome c) gene, the two catalase genes have been reported to be controlled positively by oxygen and hence and negatively by glucose repression (18).…”
mentioning
confidence: 99%